2019
DOI: 10.3389/fvets.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autologous Protein Solution on the Inflammatory Cascade in Stimulated Equine Chondrocytes

Abstract: Cartilage injury occurs commonly in equine athletes, often precipitating posttraumatic osteoarthritis (PTOA). Orthobiologics such as autologous conditioned serum (ACS) and autologous protein solution (APS) may be useful in decreasing posttraumatic inflammation, thereby preventing PTOA. The objective of this study was to quantify cytokine concentrations in ACS and APS and evaluate the protective effects of ACS and APS on inflamed chondrocytes cultured in vitro. We hypothesized that the combination of platelet-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 38 publications
3
29
1
Order By: Relevance
“…The results of our study showed a smaller increase in WBCs (12.1 vs. 4.9-fold increase) and a greater increase in PLTs (1.6 vs. 3.5-fold increase) compared to what has been reported by Bertone et al, most likely due to individual variations in physiologic status. In our study, ACS produced a significantly higher concentration of sTNF-R1 (p = 0.009) and TGF-β (p = 0.024), compared to APS, while another publication found that APS produced a higher concentration of TGF-β compared to ACS (11). Significant differences in cytokine concentration using different commercial kits under different physiologic conditions from the same horse has been reported with ACS (8,10), which could explain differences between studies.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The results of our study showed a smaller increase in WBCs (12.1 vs. 4.9-fold increase) and a greater increase in PLTs (1.6 vs. 3.5-fold increase) compared to what has been reported by Bertone et al, most likely due to individual variations in physiologic status. In our study, ACS produced a significantly higher concentration of sTNF-R1 (p = 0.009) and TGF-β (p = 0.024), compared to APS, while another publication found that APS produced a higher concentration of TGF-β compared to ACS (11). Significant differences in cytokine concentration using different commercial kits under different physiologic conditions from the same horse has been reported with ACS (8,10), which could explain differences between studies.…”
Section: Discussioncontrasting
confidence: 41%
“…In horses and dogs, APS has improved pain scores and reduced lameness up to 1 year after treatment (9,32). In vitro, limited anti-inflammatory effects have been observed following treatment of articular cells and/or tissues with APS (11,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, non-steroidal intraarticular therapies (NSIATs), such as biological and synthetic products, have become more popular. NSIATs have been shown to possess limited disease-modifying properties, such as slowing down disease progression and enhancing the quality of repair tissue (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Hix et al [20] reported the average concentration of IL-1Ra in APS to be 63,740 pg/ml whereas Woodell-May et al [46] noted it to be 30,853 pg/ml. The wide variation in the IL-1Ra levels of ACS and APS reported by the investigators may be due a combination of the production kit and the 24-h incubation period used during the preparation of ACS [47]. Various anabolic factors, including epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), IGF, TGF-β and the anti-inflammatory cytokines soluble tumor necrosis factor receptor type II (sTNF-RII), IL-4 and IL-10, have been noted in APS [46].…”
Section: Compositionmentioning
confidence: 99%
“…The aforementioned growth factors, which include TGF-β, PDGF, VEGF and IGF, have been shown to stimulate chondrocyte proliferation and augment articular cartilage metabolism [44,52]. Whilst it is perceived that both ACS and APS potentially mitigate the inflammatory cascade, the detailed pathways or mechanisms through which they perform these actions have not been fully described [40,45,47,53].…”
Section: Potential Mechanisms Of Action In Oamentioning
confidence: 99%